Meningkatkan Hasil Belajar Siswa Melalui Model Problem Based Learning Dalam Pembelajaran PAI Dan Budi Pekerti di SD Negeri 15 Murni - Meliyarti, Meliyarti (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This research aims to improve the learning outcomes of fourth-grade students at SD Negeri 15 Murni Panti by applying the Problem Based Learning (PBL) model in Islamic Education (PAI) on the topics of hadith about silaturrahmi and QS. At-Tin. The research was conducted in two cycles, with observations made on student engagement, teacher activity, and student evaluation results. The findings show that after applying the PBL model, student learning outcomes significantly improved. In cycle I, 62.5% of students reached the passing grade, while in cycle II, the percentage increased to 87.5%. The PBL model effectively engaged students in discussions, teamwork, and problem-solving, thereby enhancing their understanding of the material. This research contributes positively to the application of the PBL model in Islamic Education in elementary schools.